Fracturing of the Soft Rock Surrounding a Roadway Subjected to Mining at Kouzidong Coal Mine - Zhili Su; Wenbing Xie; Shengguo Jing; Xingkai Wang; Qingteng Tang (Advances in Civil Engineering)
The fracture development and distribution around the deep soft rock roadway are pivotal to any underground design. In this paper, both field investigation and numerical simulation were taken to study the fracture evolution and rock deformation of a coal mine roadway at Kouzidong mine, Fuyang, Anhui Province, China. Based on the borehole imaging technique, we found an asymmetric distribution of the fracture zone in the surrounding rock of the roadway. By analyzing the C value of the fractures in the borehole images,we found that the fracture interval distribution of the surrounding rock of the tunnel, the number of fractures will fluctuate decrease with the increase of the depth. To effectively study the fracture propagation and distribution of the roadway under longwall retreatment and roadway excavation, the global-local numerical technique was applied via FLAC3D and PFC2D. In the roadway excavation process, fractures were first formed in the shallow section of the roadway and progressively propagated toward the deeper soft rock layer; the main failure mechanism was a tensile failure. During longwall retreatment, fractures continuously developed toward the deeper soft rock layer. However, the failure mechanism transformed to shear failure. From numerical results, it can be seen that the stress concentration at the ribs was released, which led to shear failure at the roof and floor. Due to the extensive tensile cracks in the shallow section, the surrounding rock experienced expansion and fracture. The deep shear failure also induced the formation of the nonadjacent crushing zone and elastic zone, which is in line with the borehole imaging results.